Synthesis, Characterization and Growth Mechanism of PbTe@carbon Core-Shell Nanowires by One-Pot Hydrothermal Approach - Shen, Kai; Fang, Liming; Zhang, Jian; Zhang, Yi; Wu, Fei-Fei; Zhang, Pan-Nan; Ji, Ya-Ping; Jin, Cai-E; Qian, Haisheng (Asian Journal of Chemistry, 2012)
One-dimensional PbTe@carbonaceous thermoelectric core-shell nanowires has been fabricated successfully by a one pot hydrothermal process, which are obtained from reaction with lead acetate and sodium tellurite using glucose as reductive agent and carbon source at 160 ºC for 7 h. The growth mechanism of the PbTe@carbonaceous core-shell nanowires was discussed carefully, which is to some extent similar to the so called synergistic soft-hard template mechanism (SSHM). Furthermore, these PbTe@carbonaceous thermoelectric core-shell nanowires are obviously highly functionalized, which is of great importance to potential application in catalysis, wastewater treatment, infrared detectors, laser diodes and thermoelectric device, etc.